A pilot study of the efficacy and safety of bolus administration of alteplase in acute myocardial infarction. Issue 2 (August 1991) - Gemmill, J D; Hogg, K J; MacIntyre, P D; Booth, N; Rae, A P; Dunn, F G; Hillis, W S
Abstract : OBJECTIVE–To examine the efficacy, safety, and the pharmacokinetic profile of a bolus dose administration regimen of alteplase in the treatment of acute myocardial infarction. DESIGN–An open pilot study. SETTING–District general hospital. PATIENTS–33 suitable consecutive patients presenting within six hours of the onset of symptoms who satisfied the electrocardiographic criteria for acute myocardial infarction. INTERVENTIONS–Two intravenous boluses of 35 mg alteplase, 30 minutes apart. MAIN OUTCOME MEASURES–Angiographic coronary patency at 90 minutes and 24 hours. Plasma alteplase concentration-time profile and pharmacokinetic analysis. RESULTS–Coronary patency at 90 minutes: 26 of 30 arteries (87%, 95% confidence interval (CI) 74-99%). Coronary patency at 24 hours: 24 of 29 arteries (83%, CI 69-97%). Mean (SD) plasma tissue plasminogen activator (t-PA) concentration reached 4434.8 (2117.8) and 4233.3 (2217.5) ng/ml within 10 minutes of each bolus and fell to 425.8 (288.3) ng/ml between boluses. The estimated peak concentrations at two minutes after boluses were 12, 389 (8580) ng/ml and 10, 811 (6802) ng/ml. The derived pharmacokinetic variables were volume of distribution 3.11 (1.89) 1, clearance 21.3 (9.3) 1/h, half life 5.9 (1.7) minutes. CONCLUSIONS–This simple administration regimen achieved brief, high concentrations of plasma t-PA that were well tolerated. The regimen was associated with a high coronary patency rate at 90 minutes that was well maintained at 24 hours.